Monitoring the mixing of an artificial model substrate in a scale-down laboratory digester. (March 2019) - Conti, Fosca; Wiedemann, Leonhard; Sonnleitner, Matthias; Saidi, Abdessamad; Goldbrunner, Markus
Abstract: Investigating the mixing process in digesters is a necessary precursor for successful design, operation, and increased efficiency in biogas plants. However, observation of mixing in digesters under real conditions is complex and cost intensive. Based on the theory of similarity a 1:12 scale digester model is set up and an artificial chemical substrate is selected to mimic the rheology of real biomass. Different mixing regimes are configured using propellers and paddle stirrers located in varying positions. Optical and acoustic techniques are employed to observe the fluid dynamics. In this paper, the laboratory setup and the principal results on the flow velocity, power consumption and torque developed during mixing are presented and discussed. The experimental results illustrate the digester mixing quality in various propeller and stirrer configurations, and are used to validate a numeric computational fluid dynamic study. Highlights: Mixing process in digester is studied in laboratory through theory of dynamic similarity with full-scale biogas plants. A 1:12 scale digester model is set up and an artificial chemical substrate is selected. Different mixing regimes are configured using propellers and paddle stirrers. Flow velocity, power consumption and torque developed during the mixing are discussed. A computational fluid dynamic model is validated by experimental results.